If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -7) + 9 = -5 Reorder the terms: 2(-7 + x) + 9 = -5 (-7 * 2 + x * 2) + 9 = -5 (-14 + 2x) + 9 = -5 Reorder the terms: -14 + 9 + 2x = -5 Combine like terms: -14 + 9 = -5 -5 + 2x = -5 Add '5' to each side of the equation. -5 + 5 + 2x = -5 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = -5 + 5 2x = -5 + 5 Combine like terms: -5 + 5 = 0 2x = 0 Solving 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '2'. x = 0 Simplifying x = 0
| 3x^2+8xy-3y^2+19y-3=0 | | 7/5u=5 | | 46-3x=3(x+6)+8x | | 3x+58=9x-5(x+1) | | -3w+5w=6+10 | | -13x^2-9x+4=5+2x^2-x | | -x^4+9=0 | | 3w^2-15=0 | | 8x^9+8x^8-72x^7+16x^6= | | p+(-7)=31 | | 4a-3=2a+30 | | 7.5a+15=82.5 | | 4=11x+23 | | 7x-3x=2+18 | | 3h+2h=10 | | -15+6x=-15+6x | | 4n-5=8 | | 8-5+2*(4+3)= | | 2+12=-2(4x-7) | | 3(5r+5)-16= | | z+15=-9 | | 3x^9y^7+6x^7y^6+9xy=0 | | 6(x-2)-5(3x+2)=2-(x+3) | | 7w+8-6w+4=18 | | 10+3(d+2)=31 | | n/2.5=9 | | 7(x+4)=5(x-2) | | 10k^2-5=645 | | 4x-8=5x-7 | | 7z+z=7z+4 | | 12-8=w-3w | | w-4/3=8/3 |